Sonic Landscapes in the Metaverse: Exploring Immersive Audio Design in Virtual Environments - Vincenzo De Masi; Qinke Di; Siyi Li; Yuhan Song
Abstract This study examines the critical importance of audio design in crafting immersive experiences within the metaverse. The analysis focuses on key technologies driving this field, with particular emphasis on spatial audio techniques such as Head-Related Transfer Functions (HRTF) and Ambisonics, which enable precise three-dimensional sound positioning.